A battle of values: a case study of a blacklisted heritage tree represented by European silver fir Abies alba Mill. in a protected landscape in Norway. Issue 2 (3rd April 2018) - Ridbäck, Ulrika; Vike, Eva; Dietze-Schirdewahn, Annegreth
Abstract: Old trees in protected landscapes may be historically important, but in some cases problematic if naturalising. In this study, we investigated how a blacklisted heritage tree is valued in a protected landscape, focusing on its cultural history, invasiveness and general management of the area. We used one European silver fir Abies alba Mill. planted in the 1890s as a case-study plant. A historical literary approach included the landscape history, cultural values and introduction history of A. alba . We accessed management information from management plans, botanical reports and the supervisory manager. The present spreading of A. alba was recorded with GPS along transects. In an area constituting approximately 13, 600 m 2, vegetation clearing and grazing have contributed to limit the invasion of A. alba . Most offspring (88%) were less than 15 cm tall and found within 30 m of the parent in half-shade positions. A. alba belongs to the area's cultural historical identity, but has attracted more attention as a threat for plant species richness and habitats. Cultural and historical values are generally less prioritised in the management, which is, at present, mainly the responsibility of ecological conservationists. We therefore see a need for interdisciplinary collaboration to equally consider cultural and historical values.